Bacterial Community Composition in the Sea Surface Microlayer Off the Peruvian Coast - Zäncker, Birthe; Cunliffe, Michael; Engel, Anja (Frontiers in Microbiology, 2018)
The sea surface microlayer (SML) is located at the air-sea interface, with microorganisms and organic matter in the SML influencing air-sea exchange processes. Yet understanding of the SML bacterial (bacterioneuston) community composition and assembly remains limited. Availability of organic matter, UV radiation and wind speed have previously been suggested to influence the community composition of bacterioneuston. Another mechanism potentially controlling bacterioneuston dynamics is bacterioplankton attached to gel-like particles that ascend through the water column into the SML. We analyzed the bacterial community composition, Transparent Exopolymer Particles (TEP) abundance and nutrient concentrations in the surface waters of the Peruvian upwelling region. The bacterioneuston and bacterioplankton communities were similar, suggesting a close spatial coupling. Two Bacteroidetes families, the Flavobacteriaceae and Cryomorphaceae, were found to comprise the majority of SML-enriched operational taxonomic units (OTUs). The enrichment of these families was controlled by a variety of environmental factors. The SML-enriched bacterial families were negatively correlated with water temperature and wind speed in the SML and positively correlated with nutrient concentrations, salinity and TEP in the underlying water (ULW). Since TEP are known to be rapidly colonized by bacterial families, in particular, by those that we found to be enriched in the SML, TEP ascending from surface waters into the SML may be one of the mechanisms controlling bacterioneuston composition.